EVALUATION DE LA TOXICITÉ AIGUË DE L’EXTRAIT AQUEUX DES FEUILLES DE THUNBERGIA ATACORENSIS, UNE ESPÈCE NOUVELLE - Aké-Assi Emma; N'guessan Koffi; Kouassi Akossoua Faustine (European Scientific Journal, ESJ, 2015)
Thunbergia atacorensis is a new plant species, discovered in gallery forest of Atacora Province in Benin (West Africa). This beautiful shrub can be used as ornamental. Before introducing the plant in human environment, it will be necessary to know its toxicological parameters. This work was aimed to evaluate, in mice, the acute toxicity at different doses of the aqueous decoction of the plant leaves in order to prevent intoxication. The acute toxicity of leaves aqueous decoction from the plant was assessed after a process which consisted in giving orally, to mice, the crude decoction for increasing doses ranging from 900 to 4500 mg/kg of body weight (b.w.). The use of the plant extract, through oral route (or), at different doses, causes some clinical signs (agitations, poor appetite, motor difficulties and dyspnea). The results made it possible to obtain the dose at bordering on solubility which squares with the Letal Dose of 100% or LD100 (4500 mg/kg/b.w./or). The Tolerated Maximal Dose or TMD was evaluated at 900 mg/kg/b.w./or. The plant extract, administered orally, provided slight toxicity, with a LD50 of 1720.25 mg/kg/b.w./or. Thus, the experimentally found Letal Dose of 50% can justify the domestication of the plant as ornamental.